Proceedings of the Joint Workshop on Multiword Expressions and WordNet (MWE-WN 2019) 2019
DOI: 10.18653/v1/w19-5110
|View full text |Cite
|
Sign up to set email alerts
|

Without lexicons, multiword expression identification will never fly: A position statement

Abstract: Because most multiword expressions (MWEs), especially verbal ones, are semantically non-compositional, their automatic identification in running text is a prerequisite for semantically-oriented downstream applications. However, recent developments, driven notably by the PARSEME shared task on automatic identification of verbal MWEs, show that this task is harder than related tasks, despite recent contributions both in multilingual corpus annotation and in computational models. In this paper, we analyse possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…2) achieve global cross-language macro-averaged F1 scores below 0.6. Savary et al (2019a) argue that this is mainly due to the very nature of MWEs. Namely, MWEs of the general language (as opposed to specialized phenomena such as named entities and multiword terms) are mostly regular at the level of tokens (individual occurrences), but idiosyncratic at the level of types (sets of occurrences).…”
Section: Parseme Shared Task 2018mentioning
confidence: 99%
See 2 more Smart Citations
“…2) achieve global cross-language macro-averaged F1 scores below 0.6. Savary et al (2019a) argue that this is mainly due to the very nature of MWEs. Namely, MWEs of the general language (as opposed to specialized phenomena such as named entities and multiword terms) are mostly regular at the level of tokens (individual occurrences), but idiosyncratic at the level of types (sets of occurrences).…”
Section: Parseme Shared Task 2018mentioning
confidence: 99%
“…This implies strong lexicalization, that is, it is the combination of precise lexemes (and not so much of their senses) which makes a MWE. Savary et al (2019a) claim that, due to these properties, the generalization power of mainstream machine learning is relatively weak for MWE identification. This fact is confirmed by the results in the present paper, in which we outperform learning-based state-of-the-art systems using simple and interpretable rules and filters.…”
Section: Parseme Shared Task 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…However, such training resources are available only in a limited number of languages, and even with such resources, the automatic analysis of MWEs is known to be very difficult. Savary et al (2019) argues the importance of syntactic MWE lexicons for further development in this area.…”
Section: Multi-word Expressionsmentioning
confidence: 99%
“…1 In this study, we employ a simple method to identify MWEs in corpora by using MWE dictionaries instead of automatic detection. Despite the rich body of work (Constant et al, 2017), including methods developed in specialized shared tasks (Schneider et al, 2014;Savary et al, 2017;Ramisch et al, 2018), automatic MWE detection is still a hard problem (Savary et al, 2019). Ramisch et al (2012) tested several unsupervised discovery methods and reported that they performed poorly in terms of either precision or recall.…”
Section: Introductionmentioning
confidence: 99%